DNA damage induced by hydroquinone can be prevented by fungal detoxification - Pereira, Pedro (Toxicol Rep, 2014)
Hydroquinone is a benzene metabolite with a wide range of industrial applications, which has potential for widespread human exposure; however, the toxicity of hydroquinone on human cells remains unclear. The aims of this study are to investigate the cytotoxicity and genotoxicity of hydroquinone in human primary fibroblasts and human colon cancer cells (HCT116). Low doses of hydroquinone (227-454 μM) reduce the viability of fibroblasts and HCT116 cells, determined by resazurin conversion, and induce genotoxic damage (DNA strand breaks), as assessed by alkaline comet assays. Bioremediation may provide an excellent alternative to promote the degradation of hydroquinone, however few microorganisms are known that efficiently degrade it. Here we also investigate the capacity of a halotolerant fungus, Penicillium chrysogenum var. halophenolicum, to remove hydroquinone toxicity under hypersaline condition. The fungus is able to tolerate high concentrations of hydroquinone and can reverse these noxious effects via degradation of hydroquinone to completion, even when the initial concentration of this compound is as high as 7265 μM. Our findings reveal that P. chrysogenum var. halophenolicum efficiently degrade hydroquinone under hypersaline conditions, placing this fungus among the best candidates for the detoxification of habitats contaminated with this aromatic compound.